UPAYA PENANGANAN TERORISME JARINGAN AL QAEDA MELALUI KERJASAMA PAKISTAN - AMERIKA SERIKAT TAHUN 2009-2012 - Endang Simamora, Jojor; Rainy Priadarsini, Ni Wayan; Widya Nugraha, A. A. B. Surya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2016)
ABSTRACT Terrorism is oneeof the serious threats toward national security moreover international security. After 9/111tragedy, terror incidents has been increasing in many countries, one of them is Pakistan. The terror incidents escalation gives impact to the emerging problems in various aspects. To handle terrorism, Pakistan conducts several attempts to address the problem through joint cooperation with United States. This research aimed- to describe the efforts undertakenbbyyPakistan and United States to handle terrorism. This research uses the concepts of counterterrorism, counterterrorism cooperation, hard approach and soft approach. Key Words: Pakistan, United States, Counterterrorism, Counterterrorism Cooperation